Changes in milk production and milk fatty acid composition of cows switched from pasture to a total mixed ration diet and back to pasture. Issue 1 (2nd January 2016) - Rego, Oldemiro A.; Cabrita, Ana R. J.; Rosa, Henrique J. D.; Alves, Susana P.; Duarte, Vera; Fonseca, António J. M.; Vouzela, Carlos F. M.; Pires, Fernando Rocha; Bessa, Rui J. B.
Abstract: This study evaluated the changes of cows' milk fat fatty acids (FA) after transition from pasture to a total mixed ration (TMR) diet and back to pasture. Eight Holstein cows were used in a 52-d experiment divided into three periods. In period I (PI), cows grazed for 10 d and were supplemented with 5 kg head −1 day −1 of concentrate. On the 11th day, cows were moved to a barn and fed a TMR diet for the next 21 d (PII). On the 32nd day, cows were sent back to pasture for another 21 d (PIII) and received the same supplement of PI. Milk samples were taken on days 10 of PI and 2, 4, 7, 14 and 21 of PII and PIII. Total mixed ratio significantly increased dry matter intake and milk production and decreased milk fat content. Diet significantly affected the concentration of most FA in milk fat. Grazing pasture significantly increased the concentrations of 18:0, 18:1 c 9, 18:1 t 11, 18:2 c 9, t 11, 18:2 t11, c 15, 18:3 c 9, c 12, c15, iso and anteiso branched-chain FA and sums of monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA). Concentrations of 12:0, 14:0, 16:0, 15:0, 17:0, 18:2 c 9, c 12 and the sum of saturated fatty acids (SFA) significantly increased with PII diet. Most FA and FA sums took 14–21 d to stabilise in PII and only 4–7 d after transition for pasture. This evolution pattern of milk fat FA suggests that the long historical feeding regimen is a factor that impacts on the time cows take to respond to different diets by changing FA composition, probably as a result of the adaptation time of rumen microbes.